УЛС ТөРИйн ТОГТОЛцООнЫ ТУЛГаМдСан аСУУдЛУУд: СОнГОГЧдЫн Санаа БОдОЛ - С.МӨНХБАТ; Д.ГАЛСАНДОНДОГ (Politology, 2023)
The political system is the major subject of a political science.Political system, the set of formal legal institutions that constitute a “government” or a “state.” This is the definition adopted by many studies of the legal or constitutional arrangements of advanced political orders. More broadly defined, however, the term comprehends actual as well as prescribed forms of political behaviour, not only the legal organization of the state but also the reality of how the state functions. Still more broadly defined, the political system is seen as a set of “processes of interaction” or as a subsystem of the social system interacting with other nonpolitical subsystems, such as the economic system. This points to the importance of informal sociopolitical processes and emphasizes the study of political development. This article has the following priority issues. - Some core issues about political system - Core issues of Mongolian political system - Public opinion and political system - A political consensus is the best mechanism to resolve the problems.